The Differentiation and Promotion of Students’ Rights in Portugal - Veiga, Feliciano Henriques (2011)
This investigation includes a differential study (Study 1) and a quasi-experimental research (Study 2). In Study 1, the objective was to establish to what extent students’ rights existed and analyse the differentiation between students’ rights with Portuguese and immigrant mothers, throughout school years. The sample consisted of 537 students with Portuguese and immigrant mothers, distributed by different school years (7th, 9th and 11th grades). The Children’s Rights Scale (Hart et al., 1996; Veiga, 2001) was used. In Study 2, the purpose was to analyse the effects on students’ rights of the use by teachers of a communicational intervention program, supervised by school psychologists. The sample involved 7th and 9th grade students, in a total of four classes, two forming the experimental groups (n = 36) and two the control groups (n = 43); as in Study 1, the Children’s Rights Scale was used. The results indicated the effectiveness of the communicational intervention program on students’ rights and are consistent with previous studies. An implication is that psychologists and teachers, working together and taking a human rights perspective, may develop an important role in projects to promote the students’ rights.